Selected issues in the use of RegTech in the Islamic and conventional financial markets - Sherin, Kunhibava; Aishath, Muneeza; Zakariyya, Mustapha; Mohammad, Ershadul Karim; Adam Sa'ad, Auwal (Emerald Publishing, 2024)
Purpose – This study aims to explore several challenges in the use of regulatory technologies (RegTech) in Islamic and conventional financial markets and share recommendations in this regard. Design/methodology/approach – A qualitative research methodology was used to identify the existing challenges. Literature was reviewed and analyzed, and seven experts were interviewed or consulted online and their feedback examined. The judgment of the case B2C2 Ltd v Quoine Pte Ltd. was reviewed. Findings – This study reveals a lack of relevant regulatory frameworks capable of meeting some of the evolving challenges, lack of awareness among market players and lack of expertise in RegTech. The list of additional challenges includes the issue of legacy technology, the weaknesses of human programmers and the need for a multifaceted solution for compliance requirements. Research limitations/implications – This study notes the novelty of RegTech in the financial world, especially in the Islamic financial market. Thus, there is a dearth of relevant literature. This study assists relevant conventional and Islamic financial market entities and authorities in determining the potential impact of RegTech on their respective businesses and the financial system. Practical implications – This study proffers recommendations to assist in addressing the challenges facing its users and paving the way for innovative solutions that will facilitate and enhance the use of RegTech in financial markets. Regulators and other stakeholders of the financial industry will learn from the challenges identified and can review the recommendations for adoption. Apart from that, the decision of B2C2 Ltd v Quoine has practical implications for RegTech users, as the court in B2C2 Ltd v Quoine accessed the “knowledge” of the programmers of deterministic software at the time of the coding. Originality/value – RegTech can offer cost-effective and efficient means to comply with regulations and ensure the accuracy of the information provided to regulators. This study provides a better understanding of the challenges associated with its use. The recommendations include enactment of a blueprint for a digitally enabled regulatory framework, creating awareness of RegTech via stakeholder roundtable discussions, development of human talent, formulating human governance standards and finding innovative ways to manage risks.